Lily B. on the brink of cool - Kimmel, Elizabeth Cody. (New York : HarperCollins, 2003)
During her thirteenth summer, the "eventually internationally recognized writer" Lily Blennerhassett struggles to cope with life in her tremendously "uncool" family after meeting a much better one.
Includes bibliographical references (p. 241-245).
Wilson's Junior High School.
School Library Journal.
Publisher's Weekly.
5.6
5-8
Keywords: Authors -- Juvenile fiction; Family life -- Juvenile fiction; Swindlers and swindling -- Juvenile fiction; Friendship -- Juvenile fiction; Diaries -- Juvenile fiction; Authors -- Fiction; Family life -- Fiction; Swindlers and swindling -- Fiction; Friendship -- Fiction; Diaries -- Fiction; Authors -- Fiction; Family life -- Fiction; Swindlers and swindling -- Fiction; Friendship -- Fiction; Diaries -- Fiction; Authorship -- Fiction; Family life -- Fiction; Swindlers and swindling -- Fiction; Friendship -- Fiction; Diaries -- Fiction